Progress in the growth of CaCu3Ti4O12 and related functional dielectric perovskites - Singh L.; Rai U.S.; Mandal K.D.; Singh N.B. (My University, 2025)
Calcium copper titanate, CaCu3Ti4O12, (CCTO), a potential electro-ceramic is a member of a very important perovskite family and has been found to a show dielectric constant of the order of 10 4-105. It has a remarkable ability to undergo a series of cationic exchange reactions resulting in corresponding isomorphs. In the past decade there has been immense activity in the search of an isomorph of CCTO with high dielectric constant and low loss which enables its use as capacitor material for the storage of energy and miniaturization of electronic based equipment. Despite intensive research in the area there is no source of any literature that gives all the possible relevant information regarding various synthetic methods, characterizations, effect of sintering parameters (temperature, duration, and atmosphere). This review article is an effort to review the synthesis, grain growth, morphological evolution, effect of impurities, substitution and interface anisotropy on the dielectric constant, resistivity and other materials parameters. © 2014 Elsevier Ltd. All rights reserved.